2018
DOI: 10.1177/0263617418819227
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of congo red dye from aqueous solutions by prepared activated carbon with oxygen-containing functional groups and its regeneration

Abstract: This study investigates the potential use of activated carbon prepared from coffee waste (CW) as an adsorbent for the removal of congo red dye from aqueous solution. The oxygen-containing groups of activated carbon prepared from CW play an important role in dyes ions adsorption onto activated carbon prepared from CW. The activated carbon is characterized by scanning electron microscopy and Fourier transform infrared (FTIR) spectroscopy. Adsorption experiments were carried out as batch studies at different cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
88
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(122 citation statements)
references
References 47 publications
12
88
1
2
Order By: Relevance
“…It was observed that the removal of congo red is more efficient in acidic solution in which congo red dissociates to sulfonic group (ÀSO À 3 ) (electronic supplementary material, figure S13) [67]. The carbonaceous surface of CSC is positive in acidic medium, hence the induced electrostatic interactions between the dye and the adsorbent favoured the adsorption of the dye onto the CSCs [68]. Similar results have been obtained for the adsorption of congo red onto activated carbons [68,69].…”
Section: Adsorption Kineticsmentioning
confidence: 56%
“…It was observed that the removal of congo red is more efficient in acidic solution in which congo red dissociates to sulfonic group (ÀSO À 3 ) (electronic supplementary material, figure S13) [67]. The carbonaceous surface of CSC is positive in acidic medium, hence the induced electrostatic interactions between the dye and the adsorbent favoured the adsorption of the dye onto the CSCs [68]. Similar results have been obtained for the adsorption of congo red onto activated carbons [68,69].…”
Section: Adsorption Kineticsmentioning
confidence: 56%
“…Among them, adsorption has been widespread application due to its simple operation, low operating costs, and high efficiency. Carbon material is a traditional adsorbent material due to its high adsorption capacity, in which activated carbon is the most widely used as adsorbent (Abbas and Harrache, 2019; Huang et al., 2012; Lafi et al., 2019; Streit et al., 2019; Wu et al., 2019). However, most of these carbon materials are microporous structures and more expensive, which limits their application in polymer dyes removal.…”
Section: Introductionmentioning
confidence: 99%
“…Congo red molecules are positively charged (CR + ) under acidic conditions and negatively charged (CR − ) under alkaline conditions [49]. With the increase of pH, oxygen-containing functional groups (-COOH) will be negatively charged due to deprotonation (-COO − ) [50]. Therefore, we can conclude that there is electrostatic attraction between the congo red molecules and the carboxyl groups of the adsorbent at acidic pH, and electrostatic repulsion at basic pH.…”
Section: Adsorption Mechanismsmentioning
confidence: 99%